Beta-hexosaminidase splice site mutation has a high frequency among non-Jewish Tay-Sachs disease carriers from the British Isles. Issue 8 (August 1992) - Landels, E C; Green, P M; Ellis, I H; Fensom, A H; Bobrow, M
Abstract : In the course of defining mutations causing Tay-Sachs disease (TSD) in non-Jewish patients and carriers from the British Isles, we identified a guanine to adenine change (also previously described) in the obligatory GT sequence of the donor splice site at the 5' end of intron 9 of the hexosaminidase alpha peptide gene. Of 24 unrelated mutant chromosomes from 20 non-Jewish subjects (15 TSD carriers, four TSD patients, and one TSD fetus), five had mutations common in the Ashkenazi Jewish community, and 10 had the intron 9 splice site mutation. This is an unexpected result considering the diverse origin of the population of the British Isles. This mutation was not found in 28 control UK subjects or 11 Jewish carriers of known TSD mutations. Before attempting detection of unknown mutations, non-Jewish TSD carriers from the British Isles should be screened for the intron 9 donor splice site mutation as well as those mutations which predominate in the Jewish community.